"Coming out" as a lesbian-woman in Singapore. - Tan, Caryn Shan Ting. (2011)
This study aims to explore the manifold problems of “coming out” as a lesbian woman in Singapore - a dominantly hetero-normative social order. The phenomena of “coming out” is intense, traumatic and confusing. It entails life and death social stakes when one is deciding between “coming out” (or not). The implications of (not) “coming out” include living a “performative hypperreality” and the duplex epiphenomenon of an invisible and split life. This accentuates the importance of the role of the visible Singapore Lesbian Community in lesbian-women’s personal and social lives. Lesbian-women’s sui generis dilemma of “coming out” (or not) and at times, the very decision to (never) “come out” implies the existence of certain powerful social norms and forces at work. Going against these forces, is a revolutionary act of bravery symbolic of the enlightened spirit and ethos of modernity albeit with real sacrifices to be made.